2016
DOI: 10.1371/journal.pone.0156385
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Mycobacterium tuberculosis during Flexible Bronchoscopy in Patients with Unexpected Pulmonary Tuberculosis

Abstract: ObjectiveRecent guidelines recommend the use by healthcare personnel of a fit-tested N95 particulate respirator or higher-grade respiratory precaution in a patient undergoing bronchoscopy when pulmonary tuberculosis (PTB) is suspected. However, PTB may be unexpectedly diagnosed in this setting and therefore not evaluated, resulting in the unexpected exposure to Mycobacterium tuberculosis (MTB) of healthcare workers in the bronchoscopy suite. Here, we examined the incidence of unexpected exposure to MTB during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…[14] It has also been reported that 4.6% of patients without an initial suspicion of TB had an unexpected diagnosis of TB after bronchoscopy, thereby demonstrating the risk of healthcare exposure to Mycobacterium in otherwise unsuspected cases in countries with intermediate TB incidence, and potential utility of N95 or better respirators for infection control. [15]…”
Section: Bronchoscopy Suite Setup and Staff Protectionmentioning
confidence: 99%
“…[14] It has also been reported that 4.6% of patients without an initial suspicion of TB had an unexpected diagnosis of TB after bronchoscopy, thereby demonstrating the risk of healthcare exposure to Mycobacterium in otherwise unsuspected cases in countries with intermediate TB incidence, and potential utility of N95 or better respirators for infection control. [15]…”
Section: Bronchoscopy Suite Setup and Staff Protectionmentioning
confidence: 99%
“…In previous studies on bronchoscopy using radial probe EBUS [9][10][11][12][13][14][15], although most of the study patients were diagnosed with malignant disease, 3.9-11.0% of patients were eventually diagnosed with pulmonary tuberculosis, rates that are similar to that found in this study (Table 6). During conventional bronchoscopy, the probability of unexpected diagnosis of pulmonary tuberculosis is known to range from 0.3% to 1.3% in low pulmonary tuberculosis prevalence regions, and 3.7% to 9.1% in intermediate or high prevalence regions [2]. Our results suggest that the risk of healthcare personnel being exposed to Mycobacterium tuberculosis during bronchoscopy using radial probe EBUS has been underestimated, with it being as high as that on conventional bronchoscopy.…”
Section: Discussionmentioning
confidence: 69%
“…However, in some patients, pulmonary tuberculosis is unexpectedly diagnosed from bronchoscopy samples when the patient was not initially thought to be suffering from tuberculosis. 2 Previous studies reported that healthcare workers in the Republic of Korea, which is an intermediate tuberculosis prevalence region (59/100 000 persons per year, 2019), have at least a 4-6% chance of inadvertent exposure to Mycobacterium tuberculosis during conventional bronchoscopy [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…The rate of incidence of newly notified TB cases in Japan was 12.3 per 100 000 population in 2018, 3 and therefore, Japan is categorized as an intermediate TB‐burden country similar to South Korea. Na et al reported that 76 of 1650 patients were unexpectedly diagnosed with TB after undergoing bronchoscopy for suspected nontuberculous pulmonary diseases between 2011 and 2013 at Pusan National University Hospital 4 . Therefore, TB can result in the inadvertent exposure of healthcare workers to TB during diagnostic evaluation, especially during invasive diagnostic procedures such as bronchoscopy.…”
Section: Introductionmentioning
confidence: 99%